Self-assembled Janus base nanotubes: chemistry and applications - Zhang, Wuxia; Chen, Yupeng (Frontiers in Chemistry, 2024)
Janus base nanotubes are novel, self-assembled nanomaterials. Their original designs were inspired by DNA base pairs, and today a variety of chemistries has developed, distinguishing them as a new family of materials separate from DNA origami, carbon nanotubes, polymers, and lipids. This review article covers the principal examples of self-assembled Janus base nanotubes, which are driven by hydrogen-bond and π-π stacking interactions in aqueous environments. Specifically, self-complementary hydrogen bonds organize molecules into ordered arrays, forming macrocycles, while π-π interactions stack these structures to create tubular forms. This review elucidates the molecular interactions that govern the assembly of nanotubes and advances our understanding of nanoscale self-assembly in water.